2013
DOI: 10.3997/1873-0604.2013052
|View full text |Cite
|
Sign up to set email alerts
|

Joint interpretation of geoelectrical and soil‐gas measurements for monitoring CO2 releases at a natural analogue

Abstract: The development and validation of hierarchic monitoring concepts is essential for detecting and assessing possible leakages from storage formations, especially for carbon capture and storage (CCS) applications. Joint interpretation of various techniques (such as carbon dioxide (CO 2 ) concentration and flux measurements, self-potential (SP) and geoelectrical surveys) showed that the combination of geophysical methods with soil-gas analysis for mesoscale monitoring of the shallow subsurface above geologic CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…ERT is well-established and widely employed in hydrogeological applications (e.g., Loke et al, 2013;Slater, 2007). Time-lapse ERT is a strongly emerging branch in applied geophysics (Supper et al, 2014), monitoring dynamic processes such as surface water-groundwater interaction (e.g., Slater et al, 2010), salt-water intrusion (e.g., de Franco et al, 2009), and CO 2 migration (e.g., Sauer et al, 2014). In the context of DNAPL site investigations, ERT exhibits significant potential due to the typically highly resistive nature of DNAPLs relative to groundwater (Lucius et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…ERT is well-established and widely employed in hydrogeological applications (e.g., Loke et al, 2013;Slater, 2007). Time-lapse ERT is a strongly emerging branch in applied geophysics (Supper et al, 2014), monitoring dynamic processes such as surface water-groundwater interaction (e.g., Slater et al, 2010), salt-water intrusion (e.g., de Franco et al, 2009), and CO 2 migration (e.g., Sauer et al, 2014). In the context of DNAPL site investigations, ERT exhibits significant potential due to the typically highly resistive nature of DNAPLs relative to groundwater (Lucius et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other deep biosphere habitats may exist that are associated with CO 2 reservoirs in geological trapping structures, as indicated by an increase in gas flow rates after swarm earthquakes pointing to a gas release after seismically induced fracking of sealing layers (Sandig et al, 2014 ; Sauer et al, 2014 ; Schuessler et al, 2016 ; Fischer et al, 2017 ). Additionally, Kämpf and Bankwitz ( 2005 ) described dm- to m-sized cavities in sediments of the nearby Nová Ves II open-cast mine at 50 mbs (meter below surface), which developed along fluid migration pathways.…”
Section: Introductionmentioning
confidence: 99%
“…% in AA throughout the sampling (Table 1). Three different anomaly classes (after Sauer et al [42]; Table 2) were identified for CO 2 concentrations in the environments: (1) < 1 Vol. % (AA and NG), (2) 1–9.99 Vol.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the SG concentrations are slightly elevated, but the very high levels in SG5 and SG1 indicate CO 2 anomalies (following [42]). Although higher ones have been reported (e.g., [9]), these are comparable to those recorded from the actively degassing Rapolano Fault [47] and therefore may be associated with an actively degassing but unknown fault on the Goloring site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation